Meeting Paris agreement objectives will temper seabird winter distribution shifts in the North Atlantic Ocean. (20th January 2021) - Clairbaux, Manon; Cheung, William W. L.; Mathewson, Paul; Porter, Warren; Courbin, Nicolas; Fort, Jérôme; Strøm, Hallvard; Moe, Børge; Fauchald, Per; Descamps, Sebastien; Helgason, Hálfdán; Bråthen, Vegard S.; et al.
Abstract: We explored the implications of reaching the Paris Agreement Objective of limiting global warming to <2°C for the future winter distribution of the North Atlantic seabird community. We predicted and quantified current and future winter habitats of five North Atlantic Ocean seabird species ( Alle alle, Fratercula arctica, Uria aalge, Uria lomvia and Rissa tridactyla ) using tracking data for 1500 individuals through resource selection functions based on mechanistic modeling of seabird energy requirements, and a dynamic bioclimate envelope model of seabird prey. Future winter distributions were predicted to shift with climate change, especially when global warming exceed 2°C under a "no mitigation" scenario, modifying seabird wintering hotspots in the North Atlantic Ocean. Our findings suggest that meeting Paris agreement objectives will limit changes in seabird selected habitat location and size in the North Atlantic Ocean during the 21st century. We thereby provide key information for the design of adaptive marine‐protected areas in a changing ocean. Abstract : Using tracking data for 1500 seabirds of five key North Atlantic species and elaborated mechanistic modeling framework, we explored the implications of succeeding or failing to limit global warming to <2°C on seabird community‐level winter distributions. Our work predicts that global warming will likely induce substantial changes in seabird prey field distributions and energy requirements, resulting in northward distribution shifts of varying magnitude. Crucially, our broad‐scale analyses confirm that meeting Paris Agreement Objectives will limit habitat range shifts of the North Atlantic seabird community in 21st century. We thereby provide key information for the design of adaptive marine protected areas.